PARENTING PATTERNS FOR ORPHANS IN DEVELOPING CREATIVITY AT THE YPI DARUSSALAM ORPHANAGE IN PANGEAN DISTRICT, KUANTAN SENGINGI REGENCY, RIAU PROVINCE - Zuhrika; Firman; A. Muri Yusuf (Yayasan Citra Dharma Cindekia, 2021)
Parenting patterns determine the formation of each child's creativity. Creativity is a general ability to create something new, as the ability to provide new ideas that can be applied in problem solving, or as the ability to see new relationships between elements that already exist. the methodology used is a qualitative approach. The results of the study show that parenting provides creativity facilities such as sewing and sewing materials such as kaen, and caregivers teach or train how to sew to foster children chosen by caregivers, namely high school children, then caregivers include foster children in sewing training, and if foster children have how to do the sewing.